2016
DOI: 10.1186/s12968-016-0295-5
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular function and myocardial fibrosis in women with angina pectoris and no obstructive coronary artery disease: the iPOWER study

Abstract: BackgroundEven in absence of obstructive coronary artery disease women with angina pectoris have a poor prognosis possibly due to coronary microvascular disease. Coronary microvascular disease can be assessed by transthoracic Doppler echocardiography measuring coronary flow velocity reserve (CFVR) and by positron emission tomography measuring myocardial blood flow reserve (MBFR). Diffuse myocardial fibrosis can be assessed by cardiovascular magnetic resonance (CMR) T1 mapping. We hypothesized that coronary mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
3
21
0
4
Order By: Relevance
“…With all cMRF scans, the T 2 measurements were consistent across all slice positions. cMRF T 1 measurements were slightly (20–50 ms) higher in basal slices compared with medial and apical slices; similar trends in T 1 from basal to apical slices have been reported elsewhere . A larger spread in T 1 and T 2 measurements was observed in basal slices for both cMRF (MB = 1 and MB = 3) and MyoMaps.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…With all cMRF scans, the T 2 measurements were consistent across all slice positions. cMRF T 1 measurements were slightly (20–50 ms) higher in basal slices compared with medial and apical slices; similar trends in T 1 from basal to apical slices have been reported elsewhere . A larger spread in T 1 and T 2 measurements was observed in basal slices for both cMRF (MB = 1 and MB = 3) and MyoMaps.…”
Section: Resultssupporting
confidence: 83%
“…These scans required six separate breathholds (one per slice with T 1 and T 2 acquired separately) similar trends in T 1 from basal to apical slices have been reported elsewhere. 57,58 A larger spread in T 1 and T 2 measurements was observed in basal slices for both cMRF (MB = 1 and MB = 3) and MyoMaps. Figure 11 presents a similar analysis of the mean and standard deviation in T 1 and T 2 within the 16 AHA myocardial segments.…”
Section: In Vivo Cardiac Mappingmentioning
confidence: 89%
“…Our research group has recently published a study showing no association between CFVR and focal or diffuse myocardial fibrosis assessed by cardiac magnetic resonance imaging in women with angina but no obstructive CAD included in the iPOWER study . This indicates that the reduced LV contractile reserve in patients with CMD is unlikely to be explained by increased myocardial stiffness (as also supported by the lack of association found between CFVR and LV diastolic dysfunction) and other factors probably play a predominant role, for example, a supply/demand mismatch of myocardial perfusion caused by CMD.…”
Section: Discussionmentioning
confidence: 92%
“…However, CMD and diastolic dysfunction could also be linked by shared underlying factors such as LV hypertrophy and fibrosis caused, for example, by hypertension and other cardiovascular risk factors . However, as mentioned a substudy of the iPOWER multicentre study showed no association between fibrosis and CMD . Thirdly, a high filling pressure could also affect the subendocardial tissue and thereby the microvasculature causing CMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation